Structural and Optical Properties of Nanocrystalline 3, 4, 9, 10-Perylene-Tetracarboxylic-Diimide Thin Film. (25th June 2012) - El-Nahhas, M. M.; Abdel-Khalek, H.; Salem, E.
Abstract : Thin films of nanocrystalline 3, 4, 9, 10-perylene-tetracarboxylic-diimide (PTCDI) were prepared on quartz substrates by thermal evaporation technique. The structural properties were identified by transmission electron microscopy (TEM) and the X-ray diffraction (XRD). The optical properties for the films were investigated using spectrophotometric measurements of the transmittance and reflectance at normal incidence of light in the wavelength range from 200 to 2500 nm. The optical constants (refractive index n and absorption index k ) were calculated and found to be independent on the film thickness in the measured film thickness range 117–163 nm. The dispersion energy (E d ), the oscillator energy (E o ), and the high-frequency dielectric constant ε ∞ were obtained. The energy band model was applied, and the types of the optical transitions responsible for optical absorption were found to be indirect allowed transition. The onset and optical energy gaps were calculated, and the obtained results were also discussed.